The Meaning behind ???? and ???? Emoticons in Chat Applications: A Semiotic Analysis - Putri, Noni Trisna; Nurhaliza, Rani; Dewi, Lusiana Suciati (Ma'soem University, 2024)
This study aims to understand the meaning of ???? and ???? emoticons among chat app users. The use of emoticons is very common nowadays, used by people of all ages, from young to old. Emoticons are typically used in various situations to express someone's state or feelings in digital conversations. However, not everyone has the same opinion about the use of emoticons. This research aims to explore the different opinions people have about emoticons. The method used in this research is qualitative, utilizing Google Forms as a tool to collect data from respondents. This Google Forms survey was distributed to students of Universitas Subang, with 37 respondents aged between 18 and 25 years. The results of the study showed that the opinions of certain groups regarding the meaning and effectiveness of emoticon when using online chat applications do not influence other groups. Everyone has their own opinions and beliefs regarding the use of emoticons. Communication is possible with or without emojis, and the meaning of emojis depends on the context and the perspective of the sender and receiver.